GCK Gene-Body Hypomethylation Is Associated with the Risk of Coronary Heart Disease. (17th February 2014) - Xu, Limin; Zheng, Dawei; Wang, Lingyan; Jiang, Danjie; Liu, Haibo; Xu, Leiting; Liao, Qi; Zhang, Lina; Liu, Panpan; Shi, Xinbao; Wang, Zhaoyang; Sun, Lebo; et al.
Abstract : Objectives . Glucokinase encoded by GCK is a key enzyme that facilitates phosphorylation of glucose to glucose-6-phosphate. Variants of GCK gene were shown to be associated with type 2 diabetes (T2D) and coronary heart disease (CHD). The goal of this study was to investigate the contribution of GCK gene-body methylation to the risk of CHD. Design and Methods . 36 patients (18 males and 18 females) and 36 age- and sex-matched controls were collected for the current methylation research. DNA methylation level of the CpG island (CGI) region on the GCK gene-body was measured through the sodium bisulfite DNA conversion and pyrosequencing technology. Results. Our results indicated that CHD cases have a much lower methylation level (49.77 ± 6.43%) compared with controls (54.47 ± 7.65%, P = 0.018 ). In addition, GCK gene-body methylation was found to be positively associated with aging in controls (r = 0.443, P = 0.010 ). Conclusions . Our study indicated that the hypomethylation of GCK gene-body was significantly associated with the risk of CHD. Aging correlates with an elevation of GCK methylation in healthy controls.